Validitas LKS berorientasi HOTS dalam model inkuiri terbimbing pada materi alat optik dan pemanasan global - Nurmala Sari Lubis; Silvi Yulia Sari; Yenni Darvina; Renol Afrizon (PILLAR OF PHYSICS EDUCATION, 2020)
2013 curriculum revision in 2017 emphasizes the important subjects such as Strengthening Character Education (PPK), 4C skills (communication, collaboration, critical thinking, creativity), Literacy, and Higher Order Thinking Skills (HOTS). Based on observations conducted found that the implementation of the curriculum according to the demands of learning physics 2013 revision in 2017 is still lacking. Problems found included the lack of ability of the students in learning. Which gained the ability of students are 40% of Lower Order Thinkung Skiils (LOTS), 38% of Middle Order Thinking Skills (MOTS), and 20% of Higher Order Thinking Skills (HOTS). Besides, learning and teaching materials were available yet supportive learning HOTS oriented. Therefore, to improve the student’s HOTS in Physics, a resource-oriented HOTS is needed and developed, where the materials consist HOTS indicators and levels of Bloom's taxonomy revision Anderson, for HOTS category, student worksheet which is developed in this study also used guided inquiry learning model. This model was chosen because it is one of the learning models that can support the achievement of HOTS in learning. This study belongs to the type of R&D (Research and Development) by using Borg and Gall models. The research procedure consisted of potential problems, data collection, product design, design validation, the revised design, product testing, product revision, utility testing, product revision, and bulk products. The instrument used is validation sheets. This study is limited to the stages of product trials and product revision. Product trials conducted are limited trials. The validity of the product carried out by three expert. Based on the data, the validity of the results obtained by the experts with an average of 84.62% with a category that is very valid. Overall, HOTS oriented student worksheets in guided inquiry model are in the category of very valid. So,it can be used  in the process of learning physics to see it’s practicality and effectiveness.